What's the draw?: illustrating the impacts of cartoons versus photographs on attitudes and behavioral intentions for wildlife conservation. Issue 3 (4th May 2019) - Osinski, Brianna L.; Getson, Jackie M.; Bentlage, Belyna; Avery, George; Glas, Zoë; Esman, Laura A.; Williams, Rod N.; Prokopy, Linda S.
ABSTRACT: Changing attitudes and behaviors of a targeted audience are common ambitions of outreach campaigns. Anthropomorphized images are used to promote and facilitate conservation and environmental messaging. To evaluate their effectiveness as a messaging tactic, Indiana adults were surveyed to examine if attitudes and behavioral intentions (BIs) differed due to image type (cartoon vs. photograph) for three non-charismatic wildlife species. Wildlife management professionals (WMPs) were also interviewed to evaluate their perspectives. Unexpectedly, the surveyed population's increase in attitudes and BIs was species dependent and the cartoon was not unanimously better received. Only one cartoon species was able to elicit a significantly more positive measure than its photograph. WMPs highlighted the cartoon's need for mass appeal, accuracy, and clear messaging. The ability of cartoons to selectively impact attitudes, in conjunction with the support of WMPs, demonstrates that with thoughtful application, cartoons can sometimes be an effective messaging tool for non-charismatic species conservation.